Molecular Pathology of Endocrine Diseases - Hunt, Jennifer L.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The Molecular Pathology Library Series fills the gap between basic science and clinical application. Each user-friendly reference brings together diverse topics about molecular pathogenesis, diagnosis and treatment in one volume. The series serves physicians and healthcare providers in multiple disciplines who need to understand and apply molecular diagnostics and therapy to patient care; residents and fellows who integrate molecular medicine into their curricula and future practice; and basic and translational researchers who must define the impact of their research on clinical medicine.
General Endocrine Molecular Pathology -- Molecular Oncogenesis -- Systematic Autoimmune Diseases -- MicroRNAs in Endocrine Diseases -- Thyroid Diseases -- Clinical Detection and Treatment of Thyroid Diseases -- Autoimmune Thyroid Diseases -- Benign Nodular Thyroid Disease -- Fine Needle Aspiration: Present and Future -- Well-Differentiated Papillary Thyroid Carcinoma -- Well-Differentiated Thyroid Follicular Carcinoma -- Poorly Differentiated and Undifferentiated Thyroid Carcinomas -- Medullary Thyroid Carcinoma -- Unusual Thyroid Tumors -- Hematopoietic Tumors of the Thyroid -- Parathyroid Diseases -- Clinical Detection and Treatment of Parathyroid Diseases -- Nonneoplastic Parathyroid Diseases -- Neoplastic Parathyroid Diseases -- Pituitary Diseases -- Clinical Detection and Treatment of Benign and Malignant Pituitary Diseases -- Nonneoplastic and Neoplastic Pituitary Diseases -- Adrenal Diseases -- Clinical Detection and Treatment of Adrenal Disease -- Benign and Malignant Pheochromocytomas and Paragangliomas -- Benign and Malignant Diseases of the Adrenal Cortex -- Pancreatic Neuroendocrine Tumors -- Clinical Detection and Treatment of Pancreatic Neuroendocrine Tumors -- Pancreatic Endocrine Neoplasms -- Other Neuroendocrine Lesions -- Gastrointestinal Neuroendocrine Tumors -- Head and Neck Neuroendocrine Tumors -- Merkel Cell Carcinoma -- Neuroendocrine Lung Tumors.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology